Pembangunan Aplikasi Identifikasi Waktu Kawin Ternak Babi dengan Alihragam Wavelet dan Backpropagation - Dwiandiyanta, B. Yudi; Pratama W Putra, Marcellinus; Ernawati, Ernawati; Maslim, Martinus (Universitas Atma Jaya Yogyakarta, 2019)
Abstract.Pigs are one of the animals that are usually bred for pork production. In order to have the pork production which meet the high level of consumption, it is necessary to handle the mating time for the nursery process so that pigs can mate at the right time to avoid problems such as pregnancy failure. Determination of the right mating time in pigs can be decided by observing the shape and color of female pig vulva that is opened and slimy. The uniqueness of vulva in this breeding season can be analyzed and identified by using Haar Wavelet and Backpropagation neural networks. Wavelets are used to perform image feature retrieval, while Backpropagation artificial neural networks are used to create a base of knowledge to decide whether the pigs are at the right mating time. This application is a web application built by Visual Studio 2015 MVC5 framework with C # programming language. Users can use this application by using the Android application. The construction of this application aims to enable pig breeder to get the right time of mating to increase the pork production. This application will also be made for the smart phone version in order to make the detection process with this application more efficient.Keywords: Pattern Recognition, Haar Wavelet, Backpropagation, Pig Breeding.Abstrak. Babi merupakan hewan yang diternakkan untuk dimanfaatkan dagingnya. Agar produksi daging babi dapat memenuhi tingkat konsumsi yang tinggi, diperlukan penanganan waktu kawin agar babi dapat kawin pada waktu yang tepat sehingga menghindari permasalahan seperti kegagalan kebuntingan.Penentuan waktu kawin yang tepat pada babi terlihat pada bentuk dan warna vulva babi betina yang terlihat terbuka dan berlendir. Keunikan vulva ini dapat dianalisis dan dikenali polanya menggunakan alihragam Haar Wavelet dan jaringan syaraf tiruan Backpropagation. Wavelet digunakan untuk pengambilan ciri citra, jaringan syaraf tiruan Backpropagation digunakan untuk membuat basis pengetahuan untuk mengkategorikan karakter yang membuat babi dinyatakan berada dalam waktu kawin yang tepat. Aplikasi ini merupakan aplikasi web yang dibangun dengan bahasa pemrograman C#. Dibangunnya aplikasi ini bertujuan agar peternak babi dapat mendapatkan waktu yang tepat untuk mengawinkan ternaknya agar produksi babi dapat meningkat. Aplikasi ini juga dibuat pada ponsel pintar agar proses pendeteksian dengan aplikasi ini menjadi lebih efisien.Kata Kunci: Pengenalan Pola, Haar Wavelet, Backpropagation, Ternak Babi.